An Analysis of Taboo Words in Megan Thee Stallion’s Song Lyrics on Album “Fever” - Sinaga, Amelia Putrilanel; Siregar, Florence; Pasaribu, Sastha Theresia; Rangkuti, Rahmadsyah (English Language and Literature, 2023)
This article aimed to talk about taboo words in the song lyrics on Megan Thee Stallion's "fever" album. The researcher discussed the types, functions, and meanings of the taboo words used in the song lyrics by Megan Thee Stallion. The album song "fever" by Megan Thee Stallion served as the research sample, and its lyrics were found using Google. To describe the types of taboo words and the functions of taboo words, the researcher used theories from Wardhaugh and Batistella, respectively. The researcher then used dictionaries, the internet, and articles to find the definitions of taboo words in Megan Thee Stallion's song lyrics in order to support the information. Based on data analysis, it was found 442 total taboo words. The lyrics on Megan Thee Stallion's album "fever" contain the highest percentages of obscenity (36.4%), epithets (34.3%), and vulgarity (28%). Three functions were also found to have the highest percentages for the function of using taboo language. There are showing contempt (45.57%), being provocative (31.41%), and drawing attention (23%) are some examples. The use of words that mocked authority then became at the very least used.